NASAKOM DILEMMA AND THE POLITICS OF ISLAMIC ORGANIZATIONS: NU and Muhammadiyah Organizational Politics during the Guided Democracy Period [1959-1966] - Mustapa, Hasan; Hamid, Ihsan (UIN Mataram, 2024)
The political opinions of Islamic organizations throughout the Guided Democracy (1959- 66) era are diverse. For some, this is a dismal period. The rest saw this era as an opportunity to preserve Islamic dominance. Cooperative and non-cooperative politics with power are strategic options for the long-term political power of Islamic mass groups like Nahdhatul 'Ulama (NU) and Muhammadiyah. This study seeks to understand the political perspectives of Indonesia's two largest Islamic organizations in the face of the imposition of Nasakom (religious nationalist and communist) ideology during the Soekarno era. This study takes a qualitative descriptive comparative method. The study's findings suggest that, in terms of character, numerous NU figures found theological grounds to reconcile with Nasakom politics. Meanwhile, Muhammadiyah, whose members include numerous senior Masyumi officials, leans toward the opposition. An accommodating mindset helps the organization to breathe for longer. Meanwhile, the opposition faces the possibility of political stunting. In terms of impact, the two Islamic mass organizations failed to arrest the flow of authoritarianism. They attempted to survive by honoring the Great Leader of the Revolution.